Tecnología educativa - Consejo Nacional de Acreditación de Informática y Computación A.C. (México) (Consejo Nacional de Acreditación en Informática y Computación A.C, 2014)
Devoted to research and scholarship in educational technology.
Keywords: Educational technology : Mexico : Periodicals; Education : Mexico : Computer-assisted instruction : Periodicals; Technologie éducative : Mexique : Périodiques; Tecnología educativa : México : Publicaciones periódicas; Educación : Enseñanza asistida por ordenador : Publicaciones periódicas; Educational technology; Education : Computer-assisted instruction; Mexico